Emotion-based decision-making as a predictor of alcohol-related consequences in college students. (January 2022) - McClain, Lauren M.; Hultgren, Brittney A.; Geisner, Irene M.; Mallett, Kimberly A.; Turrisi, Rob; Larimer, Mary E.
Highlights: Student drinking during college can lead to significant negative consequences. Emotion-based decision-making (EBDM) predicts negative consequences from alcohol. Students with higher EBDM experienced more unique consequences from alcohol. Students with higher EBDM experienced greater frequency of alcohol consequences. Abstract: Student drinking during the college years can result in many adverse outcomes. Emotion-based decision-making (EBDM), or the use of emotional information to influence future plans and behavior, may lead to increased harmful consequences of alcohol. The current study examined both the number of types and total frequency of alcohol consequences as a function of EBDM. Undergraduate students from three large universities (n = 814) were assessed on EBDM and typical weekly drinking during their 2nd year of college, and alcohol-related consequences during their 2nd, 3rd, and 4th years. Alcohol-related consequences were operationalized both as unique types of consequences and total consequences experienced in the previous year. Latent growth modeling used EBDM in year 2 to predict unique and total alcohol consequences in years 2, 3, and 4. Students who endorsed higher levels of EBDM experienced a significantly increased total frequency of consequences over the three years, without differences in trajectory between students high and low on this construct. Participants with higher levels of EBDM experienced a significantly greater number of unique consequences at all time points, but these consequences increased at a significantly lower rate than individuals lower on this construct. Findings of this study indicate Emotion-Based Decision-Making may be a useful predictor of harmful consequences of student drinking over time.